Glutamatergic synaptic currents of nigral dopaminergic neurons follow a postnatal developmental sequence - Pearlstein, Edouard; Gouty-Colomer, Laurie-Anne; Michel, François J.; Cloarec, Robin; Hammond, Constance (Frontiers in Cellular Neuroscience, 2015)
The spontaneous activity pattern of adult dopaminergic (DA) neurons of the substantia nigra pars compacta (SNc) results from interactions between intrinsic membrane conductances and afferent inputs. In adult SNc DA neurons, low-frequency tonic background activity is generated by intrinsic pacemaker mechanisms, whereas burst generation depends on intact synaptic inputs in particular the glutamatergic ones. Tonic DA release in the striatum during pacemaking is required to maintain motor activity, and burst firing evokes phasic DA release, necessary for cue-dependent learning tasks. However, it is still unknown how the firing properties of SNc DA neurons mature during postnatal development before reaching the adult state. We studied the postnatal developmental profile of spontaneous and evoked AMPA and NMDA receptor-mediated excitatory postsynaptic currents (EPSCs) in SNc DA neurons in brain slices from immature (postnatal days P4-10) and young adult (P30-50) tyrosine hydroxylase (TH)-GFP mice. We found that somato-dendritic fields of SNc DA neurons are already mature at P4-10. In contrast, spontaneous glutamatergic EPSCs show a developmental sequence. Spontaneous NMDA EPSCs in particular are larger and more frequent in immature SNc DA neurons than in young adult ones and have a bursty pattern. They are mediated by GluN2B and GluN2D subunit-containing NMDA receptors. The latter generate long-lasting, DQP1105-sensitive, spontaneous EPSCs, which are transiently recorded during this early period. Due to high NMDA activity, immature SNc DA neurons generate large and long lasting NMDA receptor-dependent (APV-sensitive) bursts in response to the stimulation of the subthalamic nucleus. We conclude that the transient high NMDA activity allows calcium influx into the dendrites of developing SNc DA neurons.